NUEVO REGISTRO DE GEOPHIS LATIFRONTALIS (SQUAMATA: COLUBRIDAE) PARA EL ESTADO DE GUANAJUATO, MÉXICO - Hernández-Arciga, Raúl; Hernández, Carlos; López-Vidal, Juan Carlos; Villegas-Ruiz, Joaquín; Elizalde- Arellano, Cynthia (Instituto de Ecología, A.C., 2013)
We present a new record of Geophis latifrontalis for the Mexican state of Guanajuato. This specimen was collected in the municipality of Xichú, Guanajuato. Previews records of this species were reported from Moctezuma, San Luis Potosí and Pinal de Amoles, Querétaro, so this specimen extends the know distribution of this species into the western slope of the Sierra Madre Oriental.